Factors Influencing Muzakki's Decision Choosing to Pay Zakat at LAZNAS IZI North Sumatra (Study on Medan City Muzakki) - Sianipar, Amin Hilal; Nasution, Salman (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The aim of the research carried out by the authors is to analyze things that influence muzakki in zakat payments (study of muzakki in Medan city) at LAZNAS IZI North Sumatra. The type of research used in this research is hypothesis testing. The sample in this research was Muzakki LAZNAS IZI North Sumatra. The data collection technique used a questionnaire with a total of 127 respondents. The analytical method used in this research was the 1-5 linear scale analysis method. The software used to carry out the analysis is SPSS 22. Five independent variables are used in this research X1= Religious, X2= Service, X3= Income, X4= Accountability, and X5= Transparency. Meanwhile, the dependent variable used is Y = Do the factors of religion, service, income, accountability, and transparency influence muzakki in paying zakat at LAZNAS North Sumatra. The results of this research show that X1 =Religiousness, X3=Recome, and X5=Transparence have a significant positive effect on muzakki's interest in paying zakat in LAZNAS IZI North Sumatra Province.